Raman Spectroscopy and Statistical Analysis of the Silicate Species and Group Connectivity in Cesium Silicate Glass Forming System. (18th October 2015) - Osipov, Armenak; Osipova, Leyla; Zainullina, Rimma
Abstract : The Raman spectra ofx %Cs2 O-(100 − x )%SiO2 (x = 17, 22, 27, 33, and 37 mol%) glasses and melts were measured in the temperature range of 293 to 1553 K. The concentrations of theQ n species were calculated as a function of the composition and temperature based on the deconvolution analysis of the spectra. It was found that a dynamic equilibrium among structural units in the melts withx > 17 mol% can be described by disproportionation reactionQ 3 ⇔ Q 4 + Q 2 . The enthalpy of this reaction was found to be equal to 32 ± 6, 43 ± 8, 56 ± 10, and 52 ± 9 forx = 22, 27, 33, and 37 mol%, respectively. The nonideal entropy of mixing (ΔS mix ) depends on the melt temperature and increases almost linearly with increasing temperature. TheQ n, Q 2 – Q 2, andQ n, i j k l distributions withx ranging from 0 to 55 mol% were modeled using experimental data for the concentrations of theQ n units.